2016
DOI: 10.3892/mco.2016.814
|View full text |Cite
|
Sign up to set email alerts
|

Left adrenal gland metastasis of breast invasive ductal carcinoma: A case report

Abstract: Abstract. The majority of the metastatic lesions of the adrenal gland normally originate from lung cancer, colon malignant tumor, renal cell carcinoma and melanoma. However, adrenal gland metastasis that metastasize from breast invasive ductal carcinoma are extremely rare. The present study reported a rare case of left adrenal gland metastasis in a 35-year-old female who was diagnosed as breast carcinoma 5 years ago with a mass located on the left adrenal gland, which was detected during a routine examination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In our case immunoassaying confirmed the breast origin. Patients with adrenal metastasis usually are asymptomatic and start to express suprarenal gland disfunction only when most of the adrenal gland is replaced or destroyed [7,8]. Our patient underwent Laparoscopic Right Adrenalectomy which was converted to open due to the large size of the tumor.…”
Section: Discussionmentioning
confidence: 93%
“…In our case immunoassaying confirmed the breast origin. Patients with adrenal metastasis usually are asymptomatic and start to express suprarenal gland disfunction only when most of the adrenal gland is replaced or destroyed [7,8]. Our patient underwent Laparoscopic Right Adrenalectomy which was converted to open due to the large size of the tumor.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of metastatic patterns of breast cancer, Borst et al (8) reported that in a group of 2,246 patients with invasive ductal carcinoma, there were no observations of adrenal gland metastasis. This occurrence has only been demonstrated in prior case reports (3,6,(9)(10)(11)(12). Adrenal involvement usually occurs in the setting of widespread metastasis with solitary adrenal metastasis exceedingly rare (2).…”
Section: Discussionmentioning
confidence: 95%
“…From what we know, the first published case was in 2010 by Xiao-Jiao Liu et al in "Solitary adrenal metastasis from invasive ductal breast cancer: an uncommon finding" (5). We managed to find only six published cases of adrenal metastases from invasive carcinoma of no special type untill the time of writing (3,6,7,8,9).…”
Section: Discussionmentioning
confidence: 97%
“…Only few of the patients may have suprarenal gland disfunction if most of the adrenal gland is replaced or destroyed (9). Compared to metastases, primary adrenal glands malignancies such as adrenocortical carcinomas frequently secrete hormone excessively, causing certain relative symptoms (10).…”
Section: Discussionmentioning
confidence: 99%